Inhibition of N2 Fixation by N Fertilization of Common Bean (Phaseolus vulgaris L.) Plants Grown on Fields of Farmers in the Eastern Cape of South Africa, Measured Using 15N Natural Abundance and Tissue Ureide Analysis - Habinshuti, Simon J.; Maseko, Sipho T.; Dakora, Felix D. (Frontiers in Agronomy, 2021)
Inhibition of N2 fixation in N-fertilized common bean (Phaseolus vulgaris L.) plants growing on farmers’ fields in the Eastern Cape of South Africa, was measured using 15N natural abundance and tissue ureide analysis. The N-fertilized bean plants revealed greater soil N uptake, higher concentrations of nitrate in organs, low tissue ureide levels, low ureide-N, and much lower percent relative ureide-N abundance when compared to unfertilised plants. In contrast, the unfertilized plants showed greater nodule fresh weight, higher N derived from fixation (e.g. 84.6, 90.4 and 97.1% at Lujecweni fields 2, 3 and 4 respectively), increased amount of N-fixed (e.g. 163.3, 161.3 and 140.3 kg.ha-1 at Lujecweni fields 2, 3 and 4 respectively), greater ureide concentration in stems and petioles, higher % relative ureide-N abundance and low soil N uptake. We also found that the percent N derived from fixation was very high for some bean plants receiving a double dose of N fertilizer [e.g. Lujecweni field 1 (51.8%) and Tikitiki field 1 (53.3%], and quite high for others receiving a single dose of N fertilizer [e.g. Tikitiki field 2 (50.1%), Mfabantu fields 1 and 2 (45.5 and 79.9%, respectively), and St Luthberts field 1 (58.9%)]. Though not assessed in this study, it is likely that the rhizobia that effectively nodulated the N-fertilized bean plants and fixed considerable amounts of symbiotic N had constitutive and/or inducible nitrate reductase genes for reducing nitrate in nodules and bacteroids, hence their ability to form root nodules and derived high percent N from fixation in bean with added N. While single and double dose N fertilizer applications increased plant growth and grain yield compared to unfertilized bean plants, the single dose N fertilizer application produced much greater grain yield than the double dose. This indicates that farmers should stop using a double dose of N fertilizers on bean production, as it decreases yields and can potentially pollute the environment. This study has however shown that government supply of free N fertilizers to resource-poor famers in South Africa increased bean yields for food/nutritional security.